World order - Henry Kissinger (United Kingdom Penguin Random House, 2015)
Henry Kissinger offers in World Order a deep meditation on the roots of international harmony and global disorder. Drawing on his experience as one of the foremost statesmen of the modern era?advising presidents, traveling the world, observing and shaping the central foreign policy events of recent decades?Kissinger now reveals his analysis of the ultimate challenge for the twenty-first century: how to build a shared international order in a world of divergent historical perspectives, violent conflict, proliferating technology, and ideological extremism.
Includes Index
Keywords: International organization; Geopolitics